Method of calibration of the СOCOMO model by reduction of the basic equation - Batsenko, D.V. (Інститут програмних систем НАН України, 2015)
This article reviews calibration methods used for tuning software cost estimation models, peculiarities of calibration; a new method is proposed for higher accuracy calibration of the COCOMO model based on changing the quantity of effort multipliers; and the conclusions are drawn on the expediency of application of the proposed method.